Medbh McGuckian. - Faragó, Borbála (Contemporary Irish writers and filmmakers., 2014)
This book offers a wide-ranging analysis of the entire corpus of Medbh McGuckian's published work. It provides both a readable synthesis of existing criticism, in a fashion which will be generally useful to academics and students, and also offers an original contribution to the field of contemporary Irish literary studies on the basis of new research.